Effect of treated waste water intake on physiological, growth and hematological parameters in Karan-Fries, Tharparkar and Murrah female calves - RAUTELA, ANKITA; ASHUTOSH,; KUMAR, ANIL; ASHUTOSH, MANJU (The Indian Journal of Animal Sciences, 2023)
The present study was conducted to study the effect of treated effluent waste water over fresh water supply served for drinking purpose to calves on dry matter intake, water intake, growth, physiological and hematological parameters. For the study, 6-8 months old female calves (Karan-Fries (n=12), Tharparkar (n=12) and Murrah (n=12)) were selected from Livestock Research Center of ICAR-National Dairy Research Institute, Karnal. These experimental calves of each breed were distributed equally into two groups. The control group was offered fresh water and treatment group was offered effluent treated waste water for drinking purpose. The results of present study revealed that physio-chemical and microbial properties of water that were in accordance with the different drinkingwater standards such as Dairy NRC (2001), APHA EPA (2002) and BIS (1991). Karan-Fries, Tharparkar and Murrah experimental calves showed no significant difference in the water and dry matter intake when compared between treatment and control group calves. Non-significant differences were observed between control and treated groups of calves of all the three breeds with respect to physiological parameters (rectal temperature, respiration rate and heart rate) and hematological parameters (TEC, TLC, DLC, Hb and PCV). The observations of this study revealed that treated waste water did not show any deleterious effect on the physiological and health status of the calves. Therefore, treated effluent water can be recommended as drinking water to the animals in the water scarce areas.